The effect of brand, design, and price on intention to purchase mediated by quality perception at sport shoes X - Endang Ruswanti; Benny Herlambang; Moehammad Unggul Januarko (Journal of Economics, Business, and Accountancy Ventura, 2016)
Product cues have been identified as a major factor and are used by customers when they evaluate a product before deciding to buy. Customers evaluate products based on the product manual cues; generally, they use the brand, design and price, and produce quality perception and ceases on purchase intentions. This process also occurs in the prospective buyer's sport shoes X that have the largest sales in Indonesia. Therefore, the researchers are interested to test whether there is a relationship between the product cues on the quality perception and purchase intention for sports footwear products. This research was done by using a survey for the data collection, by distributing the questionnaires to 161 respondents. The data were analyzed using Structural Equation Modeling with Lisrel analysis tool. The result showed that the product cues have an influence mediated by the quality perception on purchase intentions. This study suggests that the perception of quality is as a full mediating variable between products cues and purchase intention.